2008
DOI: 10.1287/moor.1070.0276
|View full text |Cite
|
Sign up to set email alerts
|

Uniformly Efficient Importance Sampling for the Tail Distribution of Sums of Random Variables

Abstract: Successful efficient rare-event simulation typically involves using importance sampling tailored to a specific rare event. However, in applications one may be interested in simultaneous estimation of many probabilities or even an entire distribution. In this paper, we address this issue in a simple but fundamental setting. Specifically, we consider the problem of efficient estimation of the probabilities P S n ≥ na for large n, for all a lying in an interval , where S n denotes the sum of n independent, identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 17 publications
0
24
0
Order By: Relevance
“…This suggests computing P (S n > n ) via importance sampling, in which the importance distribution is exactly the one that is used in deriving the large deviations lower bound (namely in which the increments are iid with common increment distribution given by the "exponential twist" having mean ). When this optimal exponential twisting (OET) is used, it has been shown that the resulting importance sampling algorithm is "logarithmically e cient", in the sense that the logarithm of the number of simulation runs required to compute P (S n > n ) to a given relative accuracy is now o (n) in n. In fact, the number of simulation runs that is required to accurately 2 compute P (S n > n ) grows at the rate of n 1/2 (see, for instance, Theorem 1 of Glasserman and Juneja (2006), see also Bucklew (2004)). Hence, a very substantial e ciency improvement can be realized by utilizing the OET in computing such rare-event probabilities.…”
Section: Introductionmentioning
confidence: 99%
“…This suggests computing P (S n > n ) via importance sampling, in which the importance distribution is exactly the one that is used in deriving the large deviations lower bound (namely in which the increments are iid with common increment distribution given by the "exponential twist" having mean ). When this optimal exponential twisting (OET) is used, it has been shown that the resulting importance sampling algorithm is "logarithmically e cient", in the sense that the logarithm of the number of simulation runs required to compute P (S n > n ) to a given relative accuracy is now o (n) in n. In fact, the number of simulation runs that is required to accurately 2 compute P (S n > n ) grows at the rate of n 1/2 (see, for instance, Theorem 1 of Glasserman and Juneja (2006), see also Bucklew (2004)). Hence, a very substantial e ciency improvement can be realized by utilizing the OET in computing such rare-event probabilities.…”
Section: Introductionmentioning
confidence: 99%
“…For example, b n = 1 − n −ξ for any ξ > 0 satisfies (15). For each n, let g n denote the pdf of the form (13) with parameters α, a n and b n chosen as above.…”
Section: Proposed Importance Sampling Densitymentioning
confidence: 99%
“…random variables (see e.g., [23], for a queuing application; [16] for applications in credit risk modeling). This problem has been extensively studied in rare event simulation literature (see e.g., [5], [13], [15], [17], [25], [26]). Essentially, the literature exploits the fact that the zero variance importance sampling estimator for P (X n ∈ A), though unimplementable, has a Markovian representation.…”
Section: Introductionmentioning
confidence: 99%
“…First we consider a parametric family of importance sampling distributions based on mixtures-the precise form of which is given in Section 4. The mixture idea has also been used in the rare-event simulation literature for light-tailed systems; see, for instance, Sadowsky and Bucklew (1990) and, more recently, Glasserman and Juneja (2008). In the light-tailed environment, mixtures are often used for nonconvex rare events to protect the behavior of the likelihood ratio due to rogue sample paths that deviate from the most likely large deviations path.…”
Section: Introductionmentioning
confidence: 99%